Determinasi Faktor-Faktor Penyebab Turnover Intention Karyawan Di Encar Daihatsu Cabang Baturaja - Wulanda, Nourma; Irawan, Andri; Dyah Ayu Putriani; Dahlia; Tati Herlina; Titie Syahnaz Natalia (Jurnal Bisnis Darmajaya, 2024)
This study aims to analyze the factors that influence employee turnover intention at Encar Daihatsu Baturaja Branch. Turnover intention is an employee's intention to leave their job, which can have a negative impact on productivity and organizational stability. The factors that cause turnover intention (Y) are Job Insecurity (X1) and workload (X2). This research uses a quantitative approach with a survey method through questionnaires distributed to employees. The analysis technique uses multiple linear regression. The results of the analysis show that job insecurity has a significant positive effect on turnover intention. Employees who feel insecure about their job continuity are more likely to look for opportunities elsewhere. In addition, workload also has a significant positive influence on turnover intention, where high levels of workload cause stress that encourages the intention to leave the job. Simultaneously, job insecurity and workload contribute significantly to the increase in employee turnover intention. Based on the results of this study, companies are advised to reduce job insecurity by creating more transparent policies and providing job stability guarantees. In addition, more effective workload management, such as fair division of tasks and provision of additional support, can help reduce employee stress levels. Thus, turnover intention can be reduced, and employee retention can be improved.